(untitled) (PAKISTAN JOURNAL OF LAW, ANALYSIS AND WISDOM, 2023)
Power corrupts, and absolute power corrupts absolutely. Russia, once being the superpower power, stills bear the imprints of great power status. Therefore, after the collapse of great USSR, and the emergence of 15 new states on the world map, pushed Russia into an unprecedented power struggle to regain the power status once lost. To achieve the status quo, Russia has undermined the sovereignty and national interests of the states once were the part of USSR. To exercise its influence and regain its control over the lost territory of Moldova, Russia use every hard and soft power tool at hand, to contain the Europe’s influence on the Republic of Moldova. This paper is designed to reflect the Russia’s hybrid warfare in Moldova and its control over the Transnistrian region, which is used to create instability in Moldova. Moreover, this paper prescribes possible policies towards the ongoing conflict and a way to escape another war like Ukraine.